Verba Membawa “Ngaba” dalam Bahasa Bali Kajian Metabahasa Semantik - Ni Kadek Dwi Artini (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
Language is a means of communication between humans in everyday life, therefore humans are actors who determine the meaning of the communication. Balinese as the mother tongue used by Balinese people who still pay attention to the order in speaking. This can be seen from the many uses of words in Balinese which in this millennial era are starting to be abandoned. In fact, it is not uncommon for urban and rural people to not understand the language, one of which is verbs. There are many types of verbs in Balinese, but the researcher is interested in one verb, namely the verb carrying